Pulmonary hypertension leads to poor inpatient outcome in non-white patients admitted with stroke: an analysis of national inpatient sample - Jayaraman, Dilip Kumar; Kjelstrom, Stephanie; Montone, Georgia; Rajasekaran, Divya (Frontiers in Stroke, 2024)
Stroke is one of the leading causes of death and disability worldwide. Every year, about 795,000 strokes are reported in the United States, of which around 23% are recurrent. We analyzed the national inpatient sample to assess the outcomes in patient with pulmonary hypertension and ischemic stroke. Our study included 7 million inpatient discharge encounters among which 553,085 patients had ischemic stroke. Among this, 16,830 had PH and 536,255 did not have PH.female (63.8% vs. 48.8%; p < 0.0001). A higher proportion of stroke patients with PH died in the hospital (5.7% vs. 3.7%; p < 0.0001) as well as had a longer average length of stay (LOS) [6.3 days (SD 6.2) vs. 5.0 days (SD 6.8); p < 0.0001]. Our study noted that black patients with PH were younger [70.5 years (SD 13.8)]. Black patients had the longest length of stay compared to Caucasians (7.8 days SD 8.3) (p < 0.0001).